Look up: probing the vertical profile of new particle formation and growth in the planetary boundary layer with models and observations - O'Donnell, Samuel, author; Pierce, Jeffrey, advisor; Jathar, Shantanu, committee member; Kreidenweis, Sonia, committee member (Colorado State University. Libraries, 2022)
The processes of new particle formation (NPF) and growth are important contributors to cloud condensation nuclei (CCN) concentrations, and CCN are important for climate from their impact on planetary radiative forcing. While the general ubiquity and importance of NPF is understood, the vertical extent and governing mechanisms of NPF and growth in the lower troposphere are uncertain. We present a two-part analysis of the vertical profile of NPF during the HI-SCALE field campaign at the Southern Great Plains observatory in Oklahoma, USA. Firstly, we analyzed airborne and ground-based observations of four NPF events. Secondly, we used a column aerosol chemistry and microphysics model, along with the observations, to probe factors that influence the vertical profile of NPF. During HI-SCALE, we found several instances of enhanced NPF occurring several hundred meters above the surface; however, the spatio-temporal characteristics of the observed NPF made comparisons between airborne- and ground-based observations difficult. For six unique events, the model represented the observed NPF (or lack of NPF) and particle growth at the surface to within 10 nm. The model predicted enhanced NPF rates in the upper mixed layer, and this enhancement is primarily due to the temperature dependence in the NPF schemes. The simulations were sensitive to the initial vertical profile of gas-phase species from HI-SCALE, such that vertical mixing in the model either enhanced or suppressed NPF rates, aerosol number concentrations, and particle growth rates at the surface. Finally, our analysis provides insights for future field campaigns and modeling efforts investigating the vertical profile of NPF.
Keywords: climate; nucleation; SOA; NPF; aerosol; PBL